Thrombin Generation Assay in Hospitalized Nonsurgical Patients: A New Tool to Assess Venous Thromboembolism Risk?. (January 2017) - Espitia, Olivier; Fouassier, Marc; Hardouin, Jean-Benoît; Pistorius, Marc-Antoine; Agard, Christian; Planchon, Bernard; Trossaert, Marc; Pottier, Pierre
Background: Assessment of venous thromboembolism (VTE) risk is important to determine optimal primary prophylaxis in hospitalized patients. The Padua score helps to recognize patients with high VTE risk, but quantifying a VTE risk is often challenging in medical patients. Thrombin generation assay (TGA) reflects the pro-/anticoagulant balance and thus could help to better quantify VTE risk in medical hospitalized patients. Aim: To analyze the relation between TGA and VTE risk according to Padua score in medical hospitalized patients. Methods: Between May and October 2013, 105 patients were included in an unselected cohort group of patients admitted to an internal medicine department in a large, university hospital. Within the 36 hours after admission and before any anticoagulant therapy, Padua score was calculated and sample for TGA was collected for each patient. Thrombin generation assay (velocity, peak, and endogenous thrombin potential [ETP]) was performed with 1 and 5 picomol/l (pM) tissue factor (TF) reagent. Results: In patients with high Padua score (n = 29), velocity, peak, and ETP differed from patients with low Padua score. This difference was present at 1 and 5 pM TF, in ETP ( P < .0001 and P = .003 respectively), in peak ( P < .0001 in both conditions), and in velocity ( P < .0001). According to multivariate analysis, myeloid disorders, older age, higher body mass index, myocardial infarction, C-reactive protein >5 mg/L, reduced mobility with bed rest significantly increased velocity 1 pM TF value. Conclusion: Single thrombin generation measurement could help to identify patients at risk of VTE in medical hospitalized patients.